Expectations and adjustment dynamics in the specific-factors model: Correction and extension - Max Albert (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper corrects the analysis, presented in Albert and Meckl (1991), of adjustment in a dynamic specific-factors model with endogenous capital stocks, and extends it to a multi-sector setup.
Keywords: 330; Erwartungstheorie; Wirtschaftliche Anpassung; Theorie